Kinerja Akbar Khan (1556-1605 M) dalam Memimpin Dinasti Mugholdi India - Hestivik, Chelsi; Fadilah, Yosi; Yudistira, Srikandi; Roza, Ellya (VISA: Journal of Vision and Ideas, 2025)
The Mughal dynasty (1256-1858 AD) was the largest Muslim power in the Indian subcontinent, founded by Zahiruddin Babur, one of the grandsons of Timur Lenk. The Mughal Empire reached its peak during the reign of Akbar (1556-1605 AD). Akbar Khan is known as Sultan Abdul Fath Jalaluddin Akbar Khan. As one of the main rulers, Akbar was known for his policy of religious tolerance, supporting the presence of Hindus and Muslims, which became the basis for social stability under his rule. Under Akbar's rule, the sultanate not only developed politically and militarily, but also in the fields of economy, education, architecture, art, culture, and religion. This article aims to highlight the achievements of Akbar Khan, one of the kings who led the Mughal dynasty. Akbar contributed to the expansion of Mughal territory through strategic conquests, providing access to resources and increasing the wealth of the kingdom. He was also involved in administrative management and political strategy aimed at consolidating central powers, overcoming insurgencies and establishing diplomatic relations with regional powers.